Indonesia Investment Authority sebagai SWF Indonesia Untuk Meningkatkan Investasi Asing di Indonesia - Muhammad Jamaludin (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Sovereign Wealth Fund (SWF) as a special investation fund owned by the Government is onne of the 6 (six) actor that played a role in the impleentatition foreign investation in the last decades. Generlly SWF is made by a country that has a net export surplus, it’s held to mitigate the risk of fluctuation in commodity prices, also to avoid overheting economic as well as controlong the inflation by spreading their revenues through the SWF by invest it. Interestingly Indonesia which has a twin deficit (fiscal and current account) since 2012, were established an Indonesian Development Agency or Indonesian Investment Authority (INA) in 2020. Unlike the SWF in general which makes investments to a foreign country, INA was actually established to attract Foreign Investor co-operation on Sustainable Development in Indonesian. It is like the Rusiians with their Russian Direct Investment Fund (RDIF) which attract oriund US 40 billion of foreign capital through co-operation strategy in 2021.INA also expected to play their role as a sovereign investment fund and Deleveraging State enterprises. This research will discuss how SWF play their role and INA roles to increase the Investation in Indonesia.